2009
DOI: 10.1016/s1472-6483(10)60168-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different gonadotrophin priming on IVM of oocytes from women with normal ovaries: a prospective randomized study

Abstract: This study was designed to determine if the efficiency of in-vitro maturation (IVM) in women with normal ovaries can be improved by gonadotrophin administration. 400 women were randomly allocated in four groups: group A, non-primed cycles; group B, human chorionic gonadotrophin (HCG)-primed cycles; group C, FSH-primed cycles; and group D, FSH- plus HCG-primed cycles. There were significant differences in the IVM rate among the groups. In groups where HCG was used, the overall maturation rate was higher (57.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 41 publications
7
130
0
6
Order By: Relevance
“…Patients underwent an IVM cycle according to a previously described protocol [9]. Briefly, a baseline evaluation including an hormonal profile (AMH, FSH, estradiol and progesterone levels) and an ultrasound scan were performed on day 2-3 of the menstrual cycle.…”
Section: Ivm Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients underwent an IVM cycle according to a previously described protocol [9]. Briefly, a baseline evaluation including an hormonal profile (AMH, FSH, estradiol and progesterone levels) and an ultrasound scan were performed on day 2-3 of the menstrual cycle.…”
Section: Ivm Protocolmentioning
confidence: 99%
“…ROC curves were calculated in an attempt to determine a cutoff value for the serum AMH level with the first criterion of analysis being the retrieval of at least 5 immature oocytes. This oocyte number was considered as critical based on previous recent studies which have suggested that recovery of at least 5 immature oocytes are necessary to ensure the chances of achieving a pregnancy [9]. P-values<0.05 were considered significant.…”
Section: Ivm Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, it was developed as a milder treatment for infertility. In fact, immature oocytes can be retrieved in the absence of or after minimal ovarian stimulation [7]. In a fertility preservation context, this makes IVM particularly appropriate in cases in which the type of cancer and/or schedule of radio-chemotherapy discourage the application of a conventional ovarian stimulation regimen [5].…”
Section: Discussionmentioning
confidence: 99%
“…IVM was carried out using a single well petri dish containing 0.5 ml of IVM medium (Origio, Måløv, Denmark) supplemented with recombinant FSH 0.075 IU/ml (Merck Serono, Rome, Italy) and HCG 0.10 IU/ml (Merck Serono, Rome, Italy) [7]. After 30 h of culture, COCs were treated with 40 IU/ml cumulase solution (Origio, Måløv, Denmark) to remove cumulus cells.…”
Section: Case Reportmentioning
confidence: 99%